Discrete symmetries and CP violation - Sozzi, Marco S. (Oxford University Press, 2008)
The investigation of discrete symmetries is a fascinating subject which has been central in the agenda of physics research for 50 years, in several fields, and is the target of many experiments, ongoing and in preparation, all over the world. This book approaches the subject from a somewhat less traditional angle: while being self-contained and suitable to the reader who wants to acquire a solid knowledge of the topic, it puts more emphasis on the experimental aspects of the field, trying to provide a wider picture than usual and to convey the intellectual challenge of experimental physics and the related connection to phenomenology, a purpose for which the precision experiments in this field--often rather elegant and requiring a good amount of ingenuity--are very well suited...